OP0211 Ultrasound shows rapid reduction of uric acid load during a treat-to-target approach in gout patients: results from a longitudinal study (NOR-GOUT). (12th June 2018) - Hammer, H.B.; Karoliussen, L.; Terslev, L.; Haavardsholm, E.A.; Kvien, T.K.; Uhlig, T.
Abstract : Background: Ultrasound (US) has received an increasing attention in detecting uric monosodium urate (MSU) deposits, and is included as a domain in the ACR/EULAR classification criteria for gout. The OMERACT US group has developed definitions for US elementary lesions in gout including the double contour sign (DC) (deposits of crystals on the surface of cartilage), tophus (larger hypo-echoic aggregation of crystals, usually well delineated), aggregates (small hyper-echoic deposits) and erosions. MSU deposits may be found in many different regions with some predilection sites, but only a few small studies have explored the decrease of deposits during treatment. Objectives: To explore by US the longitudinal resolution of MSU deposits during a treat-to-target approach with urate lowering therapy (ULT) in patients with gout. Methods: In a prospective observational study, patients with crystal-proven gout were included if they presented after a recent gout flare and had increased serum urate levels (>360 μmol/L/>6 mg/dl). In a treat-to-target approach using ULT and increasing drug doses with monthly follow-up until treatment target was met (<360 μmol/L, or <300 μmol/L if clinical tophi). An extensive US assessment was performed (GE E9 machine, grey scale 15MHz) at baseline and after 3, 6 and 12 months to detect MSU deposits, using the OMERACT definitions for DC, tophi and aggregates with bilateral assessment of radiocarpal joints, MCP 2, insertion of triceps and quadriceps, proximal and distal patellar tendon, the Achilles tendon and cartilage of distal femur (maximal flexed knee) and the talar cartilage of tibiotalar joint and MTP 1 joint. The degree of elementary lesions was semi-quantitatively scored 0–3 (0=none, 1=possible, 2=certain, 3=major deposits). Sum scores of DC, tophi and aggregates, as well as total sum score of all lesions, were calculated for each visit. Changes from baseline were explored by paired samples T-test and response by Standardised Response Mean (SRM). Results: 161 patients were included at baseline (93.3% men, mean (SD) age 57.0 (14.1) years, disease duration 8.0 (7.7) years). The mean (SD) serum urate level decreased from 487 (82) μmol/L at baseline to 312 (52) μmol/L at 12 months, with 72% reaching the target at 3 months, and 84% at 12 months. Sum scores of deposits decreased over 12 months (table 1, with*=p<0.05, **=p<0.001), and the numeric decrease was largest for DC (figure 1). SRM from baseline to 3, 6 and 12 months was 0.73, 1.02 and 1.26 for DC, 0.06, 0.57 and 0.91 for tohpi and 0.20, 0.51 and 0.66 for aggregates. Conclusions: During a treat-to-target approach with ULT all deposits decreased, and most extensively for DC. This study shows that reduction of the uric acid load in gout during treat-to-target ULT can be visualised by US, and that DC may be the most sensitive to change. Disclosure of Interest: None declared